Morphology Controlled Synthesis of Composition Related Plasmonic CuCdS Alloy Nanocrystals - Gao, Yan; Wang, Lei; Tian, Guimin; Zang, Shuaipu; Wang, Hongzhe; Niu, Jinzhong; Li, Lin Song (Frontiers in Chemistry, 2020)
Cu-based ternary alloy nanocrystals have emerged for extensive applications in solar cells, light-emitting devices (LEDs), and photoelectric detectors because of their low-toxicity, tunable band gaps, and large absorption coefficients. It is still an enormous challenge that regulating optical and electrical properties through changing their compositions and shapes in alloy nanocrystals. Herein, we present a facile method to synthesize CuCdS alloy nanocrystals (NCs) with tunable compositions and shapes at relatively low temperature. Different morphologies of monodisperse CuCdS nanocrystals are tailored successfully by simply adjusting the reaction temperature and Cu:Cd precursor molar ratio. The as-synthesized nanocrystals are of homogeneous alloy structures with uniform obvious lattice fringes throughout the whole particles rather than heterojunction structures. The localized surface plasmon resonance (LSPR) absorption peaks of CuCdS NCs are clearly observed and can be precisely tuned by varying the Cu:Cd molar ratio. Moreover, current–voltage (I–V) behaviors of different shaped CuCdS nanocrystals show certain rectification characteristics. The alloy CuCdS NCs with tunable shape, band gap, and composition, possess a potential application in optoelectronic devices.